Counterspy : Memoirs of a Counterintelligence Office in World War II and the Cold War - Cutler, Richard W. (Book collections on Project MUSE., 2004)
During World War II and the beginning of the Cold War, Richard W. Cutler was an officer with the elite X-2 counterintelligence branch of the Office of Strategic Services (OSS) and with its successor, the Strategic Services Unit (SSU). Counterspy offers a rare firsthand account of the secret war against Hitler and the postwar competition with the Soviets for German intelligence assets. While with X-2, Cutler analyzed the super-secret Ultra intercepts and vetted agents about to be sent into Nazi Germany. Cutler provides an insightful overview of OSS operations during the war and their contributio.